Aktivitas antidislipidemia Tepung tempe dan susu kedelai pada profil lipid tikus diabetes yang diinduksi streptozotocin - Kartika Nugraheni; Siti Harnina Bintari (Alma Ata University Press, 2016)
ABSTRACTBackground : dyslipidemia increases risk of cardiovascular disease on diabetes patients. Soybean contain many bioactive compounds which can help control lipid profile.Objectives : analyze the difference between fermented soybean (tempe flour) and unfermented soybean (soymilk) on lipid profile in diabetic rats.Methods : thirty male sprague dawley rats divided into 3 groups (1) diabetic control (2) tempe flour 1,8 gr (3) soymilk 1,35 gr. Tempe flour and soymilk were given for 28 days. Profile lipid measured including total cholesterol, triglycerides, LDL cholesterol and HDL cholesterol. The data then were analyzed using Anova with confidence level of 95%.Results : the decrease values of total cholesteril, triglycerides and LDL cholesterol were better in tempe flour group (p<0,05). In addition, tempe flour group also showed better increase in the value of HDL cholesterl (p<0,05)Conclusion :fermented soybean (tempe flour) showed better antidyslipidemic activity than unfermented ones